Student Perception of English Club in Improving Students’ Speaking Skills - Vadriani, Vera; Mulyani, Sri; Nurwahida, Nurwahida; Ardin, Hardiani (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this study was to find out the students’ perceptions of the English club in improving students’ speaking ability at Institut Parahikma Indonesia. The researchers utilized a qualitative method. The participants of this study were five students from English Education Department, Institut Parahikma Indonesia, Gowa. Semi-structured interview, documentation, and participant observation were used to collect the data. The collected data were analyzed by using the interactive data analysis of Miles, Huberman, and Saldana (2014). The findings show that there are three categories of students’ perceptions namely the reasons, the benefits and the challenges of students in joining English club. The reasons of students in joining English club are divided into two themes namely to practice English a lot especially speaking skill and to improve all English skills. On the other hand, the benefits of joining English club consist of several themes that includes building students’ self-confidence, deepening understanding of diverse issues, improving English sub-skills such as vocabulary, pronunciation and grammar; and practicing speaking English in a more comfortable environment. In addition, this research also found some challenges in joining English club that include the difficulty in dealing with the topics, and the difficulty of being a leader in a group.